2005
DOI: 10.1080/00365520510015683
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the small bowel in Crohn's disease

Abstract: MRI using the current technique is preferable to conventional enteroclysis because of superior demonstration of the entire small-bowel pathology, low level of patient discomfort and absence of radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…However, the extent of inflammation need not be extensive; indeed, while the majority of patients with SpA have intestinal inflammation [1], only a minority develop frank IBD. Likewise, in our study, the MRI findings were subtle, and none showed the extensive complications previously reported in IBD patients [9,10], and thus none of the patients were diagnosed with IBD on the basis of the MRI. Tumor necrosis factor (TNF) inhibitors differ in their capacity to treat established IBD, with etanercept less efficacious as compared to some of the TNF monoclonal antagonists [23,24].…”
Section: Resultssupporting
confidence: 67%
“…However, the extent of inflammation need not be extensive; indeed, while the majority of patients with SpA have intestinal inflammation [1], only a minority develop frank IBD. Likewise, in our study, the MRI findings were subtle, and none showed the extensive complications previously reported in IBD patients [9,10], and thus none of the patients were diagnosed with IBD on the basis of the MRI. Tumor necrosis factor (TNF) inhibitors differ in their capacity to treat established IBD, with etanercept less efficacious as compared to some of the TNF monoclonal antagonists [23,24].…”
Section: Resultssupporting
confidence: 67%
“…Clinically useful MRI evaluation of the bowel has only been available since the late 1990s 24. MRI has several advantages over CT for the patient with Crohn’s disease:21 24 28 submucosal enhancement can differentiate active inflammation from wall-thickening alone; and improved soft tissue contrast gives better visualisation of fistulae and peri-anal disease. MRI is radiation-free, which allows for safe real-time magnetic resonance fluoroscopy if required.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological bowel wall enhancement was defined as visually increased intensity of the bowel wall compared to normal bowel wall after intravenous gadolinium and the finding was confirmed with ROI measurements [6]. Bowel stenosis was defined as more than 60% narrowing of bowel lumen compared to adjacent normal bowel [7][8][9].…”
Section: Mri Evaluationmentioning
confidence: 99%